Insecticides, Honey Bee Losses and Beekeeper Advocacy in Nineteenth-Century Ontario - Bonnell, Jennifer (Ontario History)

(untitled) (The Ontario Historical Society, 2020)
This article examines the debates that surrounded honey bee poisoning in the southern Ontario in the 1890s and early 1900s. It follows the efforts of beekeepers and supportive entomologists to press for toxicity studies, negotiate with neighbouring farmers, and advocate for legislative and educational remedies. Debates over such poisonings reveal the strained relationship between beekeepers and fruit growers in this period, and highlight the inconsistency of grower knowledge about the value of honey bees to their crops. Efforts to understand the poisoning problem and to protect honey bees from harm resulted in scientific studies that not only established the toxicity of early insecticides to honey bees, but also resulted in greater understanding of the role of honey bees in pollination. Finally, these debates illuminate the role of beekeepers as early advocates for environmental protection.